2015
DOI: 10.1159/000430226
|View full text |Cite
|
Sign up to set email alerts
|

Three Circulating Long Non-Coding RNAs Act as Biomarkers for Predicting NSCLC

Abstract: Background/Aims: Circulating long non coding RNAs (lncRNAs) have emerged recently as major players in tumor biology and may be used for cancer diagnosis, prognosis, and as potential therapeutic targets. We explored circulating lncRNA as a predictor for the tumorigenesis of non-small-cell lung cancer (NSCLC). Methods: In this study, we applied a lncRNA microarray to screen for a potential biomarker for NSCLC, utilizing RT-PCR (ABI 7900HT). A multi-stage validation and risk score formula detection analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 25 publications
0
47
0
Order By: Relevance
“…To detect NSCLC and determine its prognosis, many biomarkers, including lncRNAs, have been developed [29-32]. For example, MALAT-1 promoted the proliferation and metastasis of NSCLC and acted as an independent positive marker for poor prognosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…To detect NSCLC and determine its prognosis, many biomarkers, including lncRNAs, have been developed [29-32]. For example, MALAT-1 promoted the proliferation and metastasis of NSCLC and acted as an independent positive marker for poor prognosis [33].…”
Section: Discussionmentioning
confidence: 99%
“…In favor of this prospect, although no lncRNAs were reported in the bodily fluids of patient with OC, recent studies have identified elevated plasma lncRNA levels in patients with other cancer types such as non-small-cell lung cancer [83], hepatocellular carcinoma [84], thyroid cancer with lung metastases [85], esophageal squamous cell carcinoma [86], and renal cell carcinoma [87].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…LncRNAs are a class of non-coding RNA greater than 200 nucleotides with no protein-coding potential [5]. LncRNAs play critical roles in numerous biological processes, such as epigenetic regulation, nuclear import, cell cycle control, imprinting, differentiation, alternative splicing, RNA decay and transcription [6, 7]. Recent studies have revealed that the expression of lncRNAs is frequently dysregulated in cancers including NSCLC, and is usually correlated with cancer progression, metastasis and poor prognosis [8, 9].…”
Section: Introductionmentioning
confidence: 99%